A review on recent advances in the electrochemical reduction of CO₂ to CO with nano-electrocatalysts - Poon, Kee Chun (2023)
The electrochemical reduction (ECR) of CO2 is a powerful strategy to reduce the world's carbon footprint by converting CO2 to useful products such as CH3OH and CO. Recent techno-economic analysis has found that for the electro-conversion of CO2 to be adapted for practical use, the main products formed from this reaction need to be low-order, such as CO. This review summarizes recent progress in the ECR of CO2 to CO on nano-electrocatalysts (noble, non-noble metals and carbon nanomaterials) and provides the limitations and challenges that each electrocatalyst faces. It discusses the mechanism behind the performance of the electrocatalysts and offers the potential future prospects of the ECR process.